2019
DOI: 10.21037/jtd.2019.07.14
|View full text |Cite
|
Sign up to set email alerts
|

Delayed traumatic diaphragmatic rupture: diagnosis and surgical treatment

Abstract: Background: To investigate the diagnosis and surgical therapy of delayed diaphragmatic rupture.Methods: Forty patients with traumatic diaphragmatic rupture with delayed presentation and diagnosis were collected in Peking Union Medical College Hospital from 2000 to 2018, and a retrospective analysis was performed. Results: In all forty patients, 36 (90%) patients had a traumatic past history, and 32 (80%) patients had clinical manifestations when diagnosed. Left-sided diaphragmatic rupture was found in 32 (80%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 7 publications
0
35
0
2
Order By: Relevance
“…In cases of delayed diagnosis, an alternative transthoracic approach may offer some benefit because intra-abdominal adhesions and inflammation may lead to a more difficult repair via an abdominal approach [4]. In a recent retrospective analysis of 40 patients with a delayed diagnosis of traumatic diaphragmatic rupture, Zhao et al found 38 (95%) patients were successfully repaired with a thoracotomy approach, with a recurrence rate of 2.6% at 2-yearsfollow-up, which was repaired with a polypropylene mesh to decrease the tension via a thoracotomy approach [12]. However, as pointed out by Furak et al, multiple approaches can be utilized for chronic traumatic diaphragmatic rupture, including transthoracic, transabdominal, thoracoabdominal, or minimally invasive thoracoscopy, and the choice mainly depends on surgeon experience [4].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of delayed diagnosis, an alternative transthoracic approach may offer some benefit because intra-abdominal adhesions and inflammation may lead to a more difficult repair via an abdominal approach [4]. In a recent retrospective analysis of 40 patients with a delayed diagnosis of traumatic diaphragmatic rupture, Zhao et al found 38 (95%) patients were successfully repaired with a thoracotomy approach, with a recurrence rate of 2.6% at 2-yearsfollow-up, which was repaired with a polypropylene mesh to decrease the tension via a thoracotomy approach [12]. However, as pointed out by Furak et al, multiple approaches can be utilized for chronic traumatic diaphragmatic rupture, including transthoracic, transabdominal, thoracoabdominal, or minimally invasive thoracoscopy, and the choice mainly depends on surgeon experience [4].…”
Section: Discussionmentioning
confidence: 99%
“…Only 20% of blunt traumatic diaphragmatic injuries occur on the right side [2,3,[5][6][7]. The functional anatomy of the diaphragm is the reason behind both the rarity and the diagnostic difficulty of right-sided traumatic diaphragmatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when right-sided diaphragmatic ruptures do occur, the dome of the liver can act as a seal of the diaphragmatic defect. This poses significant challenges to the early radiological visualization of the injury and, in association with a lack of immediate symptoms, can be falsely reassuring [6,8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Thus, for a delayed diaphragmatic rupture, it was also hypothesized that most patients with delayed diaphragmatic ruptures had no acute TDR. The diaphragmatic muscle became devitalized several days or months after the initial injury 7,20 resulting in its later lysis. 21 Therefore, X ray of chest is often not diagnostic initially due to slow herniation of abdominal contents through the diaphragm and requires follow up with serial X Rays 6,22 or CTs if they are available.…”
Section: Section: Surgerymentioning
confidence: 99%